Occupational stress among teachers in the goverment aided Chinese committee primary schools (Grade A) in zone two urban district area of Kuching, Sarawak - Chin, Ngien Siong. (2002)
Numerous studies have shown that teachers serve one of the most stressful occupations. This study sought to contribute to a better understanding of occupational stress in teaching by investigating the level of stress, the main stressors, and the differences within the level of stress based on demographic variables.